ANALISIS FAKTOR KESIAPAN TEKNOLOGI DAN KEMAUAN UNTUK SEHAT YANG MENJADIKAN WANITA BERNIAT MENGGUNAKAN APLIKASI KESEHATAN FLO HEALTH - Mu’izzati, Fama Ashfa; Setyawan, Didik; Sugiyarmasto, Sugiyarmasto; Zailani, Abdullah (Surakarta Management Journal, 2024)
This study aims to analyze women's intentions to use the Flo Health menstrual calendar application through factors forming intentions so that women care more about the stability of their menstrual cycle and quality of life. This research used a sample of 214 respondents from a questionnaire distributed online. The sampling method uses non-probability sampling with a purposive sampling approach. Hypothesis testing was carried out using SEM (Structural Equation Modeling) analysis. The research findings show four supported hypotheses and one unsupported hypothesis, the perceived usefulness variable directly influences the intention to use. Technology readiness, health self-efficacy, self health awareness directly influence the variable perceived usefulness as a mediating variable. The self-reported health condition variable does not have a significant effect on the perceived usefulness variable.